Validation of Atomic Absorption Spectrometry Method for Contamination Determination of Lead (Pb) and Cadmium (Cd) in Methanol Extract and Product of Curcuma xanthorrhiza Roxb. - Dedi Hanwar; Devi Eka Nitoviani; Andi Suhendi (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2017)
The validity of atomic absorption spectrometry method for lead (Pb) and cadmium (Cd) determination in methanol extract and product of Curcuma xanthorrhiza was unknown. The aim of this work is to determine the validity of atomic absorption spectrometry method for Pb and Cd determination in methanol extract and product of Curcuma xanthorrhiza. Digestion process was done by wet digestion method and its results were read by atomic absorption spectrometry at a wavelength 217.0 nm for Pb and 228.8 nm for Cd. Validation results found % recovery of Pb and Cd respectively were 87.16% ± 0.38 (RSD 0.42) and 89.10% ± 0.06 (RSD 0.07) in methanol extract of Curcuma xanthorrhiza, 92.62% ± 0.24 (RSD 0.26) and 100.16% ± 0.07 (RSD 0.07) in Curcuma xanthorrhiza product. Precision test found the RSD value for Pb in the methanol extract and product of Curcuma xanthorrhiza were 0.02 and 0.14 respectively, but the RSD value for Cd were not detected. The linearity test results of Pb and Cd standar solution were 0.9998 and 0.9979. The LOD for Pb and Cd were 0.4 ppm and 0.1 ppm, and the LOQ were 1.3 ppm and 0.5 ppm respectively. Based on the % recovery results, the method of Pb and Cd determination by atomic absorption spectrometry is valid for methanol extract and product of Curcuma xanthorrhiza. The levels of Pb in extract and product of Curcuma xanthorrhiza were 2.10 ± 0.001 mg/kg and 4.34 ± 0.001 mg/kg respectively, but the levels of Cd in both samples did not detected.